TAPHONOMY OF EEMIAN MARINE MOLLUSCS AND ACORN BARNACLES FROM EASTERN ARKHANGELSK REGION, NORTHERN RUSSIA - Nielsen J.K.; Funder S. (My University, 2003)
Marine Eemian deposits along the Pyoza river and its tributary Varchuska, Arkhangelsk region, constitute successions of muddy and sandy facies with rich macrobenthic fauna dominated by bivalves and barnacles. Taphonomic features formed by abrasion, disarticulation, dissolution, fragmentation, bioerosion and encrustation define taphofacies for a palaeoenvironmental model. Five bivalve taphofacies and three barnacle taphofacies could be distinguished. Both bivalves and barnacles are poorly preserved in foreshore/shoreface environments, as the shells were subjected to extensive transportation by currents. The shells were best preserved in offshore environments, where rapid episodic sedimentation enabled within-habitat preservation, in some cases even preservation in life position. Barnacles are absent from the most clay-rich offshore deposits, probably because of clogging of filters by turbidity and lack of suitable substrate. Such dissimilarities suggest that the number and distribution of taphofacies may depend on which fossil groups are used. Interspecific variability may exist within the individual taphofacies. The barnacles, for example, tend to be better preserved than the mussel Mytilus edulis, although both are fixosessile suspension feeders. This indicates that not only life habits but also intrinsic shell properties influence preservation. Thus, taphofacies analyses should combine data on taphonomic features, specific life habit and shell properties to determine overall preservation patterns. In that way, taphofacies analyses may form a powerful tool for palaeoenvironmental analyses of marine deposits.
Keywords: Cirripedia; Mollusca; taphofacies; Eemian; Quaternary; Arkhangelsk; Cenozoic::Quaternary; Кайнозой::Четвертичная